Opportunities and Challenges of Urban Agriculture for Sustainable City Development - Van Tuijl, Erwin; Hospers, Gert-Jan; Van Den Berg, Leo (European Spatial Research and Policy, 2018)
Urban Agriculture (UA) has gained popularity in cities all over the world. In this paper, we explore the concept of UA and discuss it along various locational and strategic dimensions. The article aims to provide insights into the chances and challenges of UA for sustainable city development. By making use of case examples from cities worldwide we show that UA can contribute to the social, environmental, and economics pillars of sustainable city development. However, there are limitations which should be taken into account for cities that want to invest in urban agriculture.